Protective Effects of Bacillus amyloliquefaciens 40 Against Clostridium perfringens Infection in Mice - Jiang, Zipeng; Li, Wentao; Su, Weifa; Wen, Chaoyue; Gong, Tao; Zhang, Yu; Wang, Yizhen; Jin, Mingliang; Lu, Zeqing (Frontiers in Nutrition, 2021)
The study aimed to investigate the protective effects of Bacillus amyloliquefaciens (BA40) against Clostridium perfringens (C.perfringens) infection in mice, and we also want to compare it with the Bacillus subtills PB6 to detect which one has the best preventive effect. A total of 24 five-week old male C57BL/6 mice were randomly divided into four groups. BA40 and PB6 group were orally dosed with resuspension bacteria (1.0 × 109 CFU/mL), once a day, from day 1 to day13, respectively, while mice in the Control and Infected group were pretreated with an equal volume of PBS in the same manner. Mice in Infected group, PB6 + Infected group and BA40 + Infected group were orally challenged with 1.0 × 109 CFU/mL of Clostridium perfringens type A in day 11, whereas the control group was orally dosed with PBS. The results showed that BA40 group ameliorate intestinal structure damage caused by C.perfringens infection. Furthermore, the inflammatory responses were detected in Infected group and it also alleviated (P < 0.05) by BA40 treatment, including the concentrations of IL-1β, IL-6, TNF-α and IgG in serum and SIgA in colon, and NO production and iNOS activity in jejunum. Similarly ,the cytokines were detected by qPCR in the mRNA levels, and results is consistent with ELISA kits. Besides, C.perfringens infection induced apoptosis by increasing the expression of Bax, p53 and decreasing Bcl-2 expression, which was reversed by BA40 and PB6 treatment (P < 0.05). Moreover, BA40 restored the intestinal microbiota imbalance induced by C.perfringens infection, characterized by improving the relative abundance of Verrucomicrobiota (P < 0.05) and decreasing the relative abundance of Bacteroidetes (P < 0.05) in phyla level, and Infected group increased the relative abundance of some pathogens, such as Bacteroides and Staphylococcus (P < 0.05) in genus level. BA40 also activated the metabolic pathways of the microbiota in C.perfringens infected mice, including Purine metabolism, 2-Oxocarboxylic acid metabolism and Starch and sucrose metabolism. In conclusion, BA40 can effectively protect mice against C.perfringens infection than PB6 through improved composition and metabolic pathways of the intestinal microbiota, intestinal structure, inflammation and anti-apoptosis.